Blue-Light Filtering Spectacle Lenses: Optical and Clinical Performances - Leung, Tsz Wing; Li, Roger Wing-hong; Kee, Chea-su (PLOS ONE, 2017)
Purposes To evaluate the optical performance of blue-light filtering spectacle lenses and investigate whether a reduction in blue light transmission affects visual performance and sleep quality. Methods Experiment 1: The relative changes in phototoxicity, scotopic sensitivity, and melatonin suppression of five blue-light filtering plano spectacle lenses were calculated based on their spectral transmittances measured by a spectrophotometer. Experiment 2: A pseudo-randomized controlled study was conducted to evaluate the clinical performance of two blue-light filtering spectacle lenses (BF: blue-filtering anti-reflection coating; BT: brown-tinted) with a regular clear lens (AR) serving as a control. A total of eighty computer users were recruited from two age cohorts (young adults: 18–30 yrs, middle-aged adults: 40–55 yrs). Contrast sensitivity under standard and glare conditions, and colour discrimination were measured using standard clinical tests. After one month of lens wear, subjective ratings of lens performance were collected by questionnaire. Results All tested blue-light filtering spectacle lenses theoretically reduced the calculated phototoxicity by 10.6% to 23.6%. Although use of the blue-light filters also decreased scotopic sensitivity by 2.4% to 9.6%, and melatonin suppression by 5.8% to 15.0%, over 70% of the participants could not detect these optical changes. Our clinical tests revealed no significant decrease in contrast sensitivity either with (95% confidence intervals [CI]: AR–BT [–0.05, 0.05]; AR–BF [–0.05, 0.06]; BT–BF [–0.06, 0.06]) or without glare (95% CI: AR–BT [–0.01, 0.03]; AR–BF [–0.01, 0.03]; BT–BF [–0.02, 0.02]) and colour discrimination (95% CI: AR–BT [–9.07, 1.02]; AR–BF [–7.06, 4.46]; BT–BF [–3.12, 8.57]). Conclusion Blue-light filtering spectacle lenses can partially filter high-energy short-wavelength light without substantially degrading visual performance and sleep quality. These lenses may serve as a supplementary option for protecting the retina from potential blue-light hazard. Trial Registration ClinicalTrials.gov NCT02821403